Luxury, heritage, and sustainability: Negotiating identity in the jewelry market - Khoury, Josiane El (International Journal of Innovative Research and Scientific Studies, 2025)
This paper explores the intersection of luxury, heritage, and sustainability through a case study of L’Atelier Nawbar, a Lebanese jewelry brand that integrates eco-conscious practices without compromising its aura of exclusivity and tradition. While luxury has historically been associated with rarity, permanence, and cultural prestige, contemporary demands for sustainability challenge brands to reconcile these values with ecological responsibility. Drawing on self-congruity theory, Kapferer’s Brand Identity Prism, and innovation resistance theory, this study examines how L’Atelier Nawbar communicates sustainability through transparency, cultural storytelling, and heritage-driven narratives. The findings reveal that sustainable practices such as upcycling, lab-grown stones, and Single Mine Origin gold are accepted by consumers when framed as extensions of tradition and identity, rather than as ruptures from them. Emotional storytelling—particularly during cultural and social crises—allows the brand to position sustainability as both culturally relevant and symbolically prestigious. The study concludes that the viability of eco-luxury lies not only in adopting sustainable materials but in aligning them with consumer self-image, cultural values, and brand identity. By embedding sustainability into heritage and identity, luxury brands can overcome consumer resistance and redefine exclusivity in line with contemporary global values.